Correction: Fluorescence imaging of a potential diagnostic biomarker for breast cancer cells using a peptide-functionalized fluorogenic 2D material. Issue 4 (18th December 2019) - Dou, Wei-Tao; Liu, Li-Fang; Gao, Jie; Zang, Yi; Chen, Guo-Rong; Field, Robert A.; James, Tony D.; Li, Jia; He, Xiao-Peng
Abstract : Correction for 'Fluorescence imaging of a potential diagnostic biomarker for breast cancer cells using a peptide-functionalized fluorogenic 2D material' by Wei-Tao Dou et al., Chem. Commun., 2019, 55, 13235–13238.